2014
DOI: 10.1080/15287394.2014.944680
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Biomarkers Associated with Blood Lead, Mercury, and Cadmium in Premenopausal Women: A Prospective Cohort Study

Abstract: Certain metals are harmful to the kidney and liver at high levels but associations with functional biomarkers at low exposure levels among premenopausal women has not apparently been evaluated. Healthy, regularly menstruating women (n=259) were followed for up to two menstrual cycles with up to 16 visits. Renal and liver biomarkers were measured in serum at each clinic visit. Cadmium (Cd), lead (Pb), and mercury (Hg) were measured in whole blood at baseline. Linear mixed models were adjusted for age, body mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 46 publications
2
36
0
1
Order By: Relevance
“…Department of Health and Human Services 2011). Epidemiological studies have confirmed its toxic effects on lung (IARC 1993), kidney (Pollack et al 2015) and bone functions (Thomas et al 2011). Additionally, numerous studies found positive associations between cadmium exposure and breast cancer (Julin et al 2012a; Julin et al 2012b; McElroy et al 2006; Nagata et al 2013; Romanowicz-Makowska et al 2011; Strumylaite et al 2011), prostate cancer (Elghany et al 1990; Julin et al 2012b; Sharma-Wagner et al 2000; Vinceti et al 2007), lung cancer (Park et al 2012; Sorahan and Lancashire 1997; Stayner et al 1992; Zhang et al 2012), and all cancer mortality (Adams et al 2012; Elinder et al 1985; Lin et al 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Department of Health and Human Services 2011). Epidemiological studies have confirmed its toxic effects on lung (IARC 1993), kidney (Pollack et al 2015) and bone functions (Thomas et al 2011). Additionally, numerous studies found positive associations between cadmium exposure and breast cancer (Julin et al 2012a; Julin et al 2012b; McElroy et al 2006; Nagata et al 2013; Romanowicz-Makowska et al 2011; Strumylaite et al 2011), prostate cancer (Elghany et al 1990; Julin et al 2012b; Sharma-Wagner et al 2000; Vinceti et al 2007), lung cancer (Park et al 2012; Sorahan and Lancashire 1997; Stayner et al 1992; Zhang et al 2012), and all cancer mortality (Adams et al 2012; Elinder et al 1985; Lin et al 2013).…”
Section: Introductionmentioning
confidence: 98%
“…However, excessive exposure to it could cause a variety of toxic effects, among which is its adverse influence on the kidney. An increasing number of studies have also indicated the unexpected effects and pathogenic mechanisms of Pb on renal function [3][4][5]. Among the various pathogenic mechanisms of renal injury, oxidative stress influences glomerular structure and function mainly depending upon the effect of reactive oxygen species (ROS) on mesangial and endothelial cells [6].…”
Section: Introductionmentioning
confidence: 99%
“…Pollack et al (2015) investigated a change in serum bilirubin levels in relationship to Cd exposure levels in 259 women, aged 18-44 yrs, and they found that doubling of blood Cd levels was associated with a fall in serum bilirubin levels by 4.9%. Colancino et al…”
Section: Study Synopsis Findingsmentioning
confidence: 99%
“…Serum bilirubin in relationships to Cd exposure levels, Pollack et al (2015), n259 healthy women (aged 18-44 yrs) in Buffalo, New York.…”
Section: Study Synopsis Findingsmentioning
confidence: 99%